Determination of Competence, Work Discipline, and Utilization of Technology towards Public Satisfaction Through Service Quality in the Fisheries Service of Karimun Regency - Syamsurizal, Syamsurizal; Ngaliman, Ngaliman; Yanti, Sri (Journal of Coastal and Ocean Sciences, 2024)
High employee competency will ensure that every task and responsibility can be completed effectively and efficiently. Good work discipline will create an orderly and productive work environment, improving the quality of services provided to the community. Technology also plays an equally important role; because of sophisticated technology, service processes can be carried out more quickly and accurately, reducing human error and increasing people's comfort in accessing public services. The research aims to determine the effect of competence, work discipline, and the use of technology on community satisfaction through service quality. The study was conducted for 5 months (March –July) at the Karimun Regency Fisheries Service. Quantitative research methods were analyzed using the Smart PLS application from questionnaire data with 201 respondents and concluded that there is a direct determination of employee competency, work discipline, use of technology, and service quality on community satisfaction in the Karimun Regency Fisheries Service area. There is a determination of employee competency in work discipline and the use of technology directly on the quality of services of the Karimun Regency Fisheries Service. It is recommended to the Head of the (Karimun Regency Fisheries Service: 1) optimize the number of employees who take part in work competency training, especially regarding increasing knowledge and skills according to the fields listed. 2) Providing training programs or seminars to improve employee work discipline regarding the importance of arriving on time, effectively using time, compliance with agency regulations, and achieving work targets. 3) Optimizing an integrated information system in providing services and basic skills using the latest technology, which can help communicate with the service user community by keeping up with the latest technological developments and meeting needs in completing tasks appropriately based on the availability of information.